Shear performance of UHPC-filled pocket connection between precast UHPC girders and full-depth precast concrete slabs. (February 2021) - Fang, Zhuangcheng; Jiang, Haibo; Xiao, Jie; Dong, Xiaotong; Shao, Tengfei
Abstract: Ultra-high-performance concrete (UHPC) has been widely utilized in civil engineering due to its superior mechanical properties and durability. However, there is limited knowledge on the interface shear behavior in UHPC composite structures. In this study, twelve push-out tests, with testing variables of the types of precast girder, the types of precast slab and the shear reinforcement ratios, were conducted to examine the shear performance of UHPC-filled pocket connection between precast UHPC girders and full-depth precast concrete slabs. Based on the analysis of the experimental results, the reinforcements across the joint could significantly improve both of the interface shear capacity and residual shear resistance. Additionally, both the precast slab types and precast girder slab types have an apparent influence on the interface shear strength. Besides, all the parameters investigated in this study played an essential role in the interface shear slippages at the ultimate stress. Furthermore, the experimental results in this study can rarely be predicted well by typical equations developed in current design codes and previous studies. Therefore, a more accurate equation was developed to predict the interface shear transfer stress between precast UHPC girder and full-depth precast concrete slab with a UHPC-filled pocket connection.